6. EVALUATION OF SURGICAL RESULTS (BRIEF PROCEDURE) ARTERYVENOUS SHUNTING FOR KIDNEY DIALYSIS AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objects: (1) Characteristics of chronic kidney disease patients at stage 4 or 5, indicated for dialysis using an arteriovenous bypass at the Department of Cardiothoracic Surgery; (2) Evaluating surgery result of arteriovenous fistula of these patients.Methodology: A retrospective description of chronic renal failure patients, who performed arteriovenous fistula surgery by appreciated procedure from 01/2023-11/2023 at the cardiovascular surgery department, Thong Nhat Hospital.Results: 38 cases (26 men, 12 women). The mean patient age was 59,5 ± 7,4 years old. Average surgery time was 72.1 minutes, hospital stay-38.3 hours, 100% material uses vessels. Good result was 97,3%. Complications: 02 infections, 01 hematomas, 02 thrombus, non perioperative death.Conclusion: Arteriovenous bypass surgery follows an abbreviated procedure at the department to shorten waiting time. Positive surgical results, suitable for simple cases; reaching effective social and management value when reducing pressure on hospitals and meeting increasing demands from patients.
Keywords: Arterioveinous shunt for hemodialysis, chronic kidney disease.